Identifikasi Pola Sebaran Ruang Terbuka Hijau (RTH) Di Kawasan Lumpur Lapindo - Nur Sinta Aulya; Moch. Shofwan (LPPM Universitas Putera Batam, 2023)
The mud disaster that has occurred in Sidoarjo Regency since May 29 2006 was an event of hot gas and mud coming out of the ground with a temperature of 100°C which has inundated several villages in Sidoarjo Regency. Before the disaster, Porong was a productive area because there were many rice fields, shops and factories. The three districts affected by the Lapindo mudflow, namely Porong District, Tanggulangin District, and Jabon District, previously in 2005, based on satellite imagery, had the form of a spreading Green Open Space (RTH). The impact that resulted from the occurrence of the Lapindo mud disaster was the occurrence of land conversion, especially in the Green Open Space (RTH) sector. Based on these problems, it is necessary to identify the pattern of distribution of green open spaces in the Lapindo Mud Disaster Area. This research discusses the distribution pattern of Green Open Space (RTH) in the Lapindo mud disaster area using the Nearest Neighbor Average (NNA) Analysis method. Based on the results of the Nearest Neighbor Average (NNA), the distribution pattern generated in the Lapindo Mud Disaster Area has a random distribution pattern (Random). Porong clustered (Clustered).